2014
DOI: 10.1001/jama.2014.9237
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Care Intervention and Postdischarge Smoking Cessation Among Hospitalized Adults

Abstract: IMPORTANCE Health care systems need effective models to manage chronic diseases like tobacco dependence across transitions in care. Hospitalizations provide opportunities for smokers to quit, but research suggests that hospital-delivered interventions are effective only if treatment continues after discharge. OBJECTIVE To determine whether an intervention to sustain tobacco treatment after hospital discharge increases smoking cessation rates over standard care. DESIGN A randomized controlled trial conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
117
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 129 publications
(128 citation statements)
references
References 37 publications
1
117
2
4
Order By: Relevance
“…We also found that studies using biochemical verification showed higher cessation rates than those without, which was seemingly contradictory to evidence that self-reported cessation rates were overestimated (Noonan et al, 2013; Rigotti et al, 2014). For instance, one study investigating the validity of self-reported cessation by a biochemical test found that 15 out of 72 self-reported quitters did not pass the urine cotinine test, resulting in an over-reporting rate of 21% (Noonan et al, 2013).…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…We also found that studies using biochemical verification showed higher cessation rates than those without, which was seemingly contradictory to evidence that self-reported cessation rates were overestimated (Noonan et al, 2013; Rigotti et al, 2014). For instance, one study investigating the validity of self-reported cessation by a biochemical test found that 15 out of 72 self-reported quitters did not pass the urine cotinine test, resulting in an over-reporting rate of 21% (Noonan et al, 2013).…”
Section: Discussioncontrasting
confidence: 87%
“…Biochemical verification was dichotomized, indicating whether self-reported smoking cessation status was verified by biochemical methods, such as examining the carbon monoxide (CO) level in exhaled air and cotinine level in saliva or urine. It has been reported that self-reported cessation rates were higher than biochemically verified rates in a given study (Noonan et al, 2013; Rigotti et al, 2014). Follow-up times reported in different units were converted to values in months, and they were further classified into three categories: up to 3 months (reference), 3 to 12 months (binary variable), and over 12 months (binary variable).…”
Section: Methodsmentioning
confidence: 68%
“…4,5 Furthermore, recent data have highlighted the potential of delivering tobacco-cessation interventions during the hospital stay, particularly when supplemented with post-discharge counseling and medication, as a particularly effective strategy to promote cessation. 6 Based on 2011 hospitalization, population, and tobacco use prevalence data, an estimated 120,000 tobacco users are admitted to Oklahoma hospitals annually. [7][8][9][10] In an effort to seize this opportunity to intervene, the Oklahoma Hospital Association (OHA), Oklahoma Tobacco Settlement Endowment Trust Fund, and select hospitals partnered to implement healthcare system changes to integrate a sustainable tobacco-cessation protocol for all tobacco-using patients.…”
Section: Introductionmentioning
confidence: 99%
“…16 This current analysis found proportionally more racial minorities in subgroups with both the highest and the lowest probabilities of cessation. This suggests that differences in cessation after discharge may be more complex than demographics and based in part on patterns of cessation predictors.…”
Section: Discussionmentioning
confidence: 49%